Effect of Work Life Balance On Intention to Stay On PT. Global Comm Indonesia With Work Engagement as a Mediation - muhammad kevin; Syahrizal (Universitas Negeri Padang, 2022)
This study aims to determine the effect of work life balance on the Intention to stay with work engagement as a mediator. The population in this study were employees of PT. GlobalCom Indonesia. While the sample used amounted to 67 employees. Data collection is done through distributing questionnaires and data processing is done through smart PLS. The results of this study indicate that work life balance has a positive and significant effect on work engagement, work engagement has a positive and significant effect on intention to stay, work life balance has a positive and significant effect on Intention to stay and work life balance has positive and significant effect on Intention to stay with work engagement as a mediating variable.